PENERAPAN PEMBELAJARAN BERDIFERENSIASI BERBASIS MODEL PROBLEM BASED LEARNING BERDASARKAN GAYA BELAJAR PESERTA DIDIK UNTUK MENGETAHUI HASIL BELAJAR PESERTA DIDIK PADA MATERI BAKTERI KELAS X-1 SMAN I TALIBURA - Gratia Aprilia, Maria; Nong Bunga, Yohanes; Hadi Jaya Putra, Sukarman (Universitas Cokroaminoto Palopo, 2024)
Based on the results of observations and interviews with biology teachers at SMAN 1 Talibura, differentiated learning based on the Problem Based Learning model based on students' learning styles has not been applied directly so that it is not possible to know the influence of students' learning outcomes from the application of learning. The purpose of this study is to determine the cognitive influence of the application of differentiated learning based on students' learning styles on class X-1 bacteria material at SMA Negeri 1 Talibura. The research method used is classroom action research (PTK) with the kurt lewin model which consists of two learning cycles. Each cycle has four main stages of activities, namely planning, acting, observation, and reflection. This study was attended by 30 people consisting of 11 men and 19 women in class X-1. The data collection technique carried out is through tests, namely pretest and posttest. The results of the study showed an increase in the percentage of learning outcomes from the first cycle by 37% to 87% in the second cycle. This increase shows that the application of the Problem-Based Learning learning model with a differentiated learning approach based on students' learning styles can improve the biology learning outcomes of students in class X-1 Phase E on Bacteria material.